A different approach to graphene-doped MnO Supercapacitor production: synthesis with different solvents - Aydın, Cihat (Niyazi BULUT, 2024)
Supercapacitors fill the performance gap between traditional capacitors and batteries. Due to their higher energy density than traditional capacitors and higher rapid charge/discharge and cycle life than batteries, supercapacitors offer a versatile solution for storing and transferring high-density energy obtained at variable times within seconds and integrating into energy transfer lines, unlike renewable energy sources. . In this study, graphene oxide (GO), which will be used to produce materials with supercapacitive properties, was synthesized by the Modified Hummers method. The produced graphene oxide (GO) was reinforced into metal oxide (MnO) solutions synthesized by the sol-gel method. As a result of the characterization processes of the obtained samples, the effects of graphene oxide (GO) and different solvents on the composite materials were examined by XRD, SEM, FT-IR, DTA-TG, UV-vis and cyclic voltammetry (CV) methods.
Keywords: Functional Materials; Fonksiyonel Malzemeler